The Mn-motif protein MAP6d1 assembles ciliary doublet microtubules - Dharshini Gopal; Juliette Wu; Julie Delaroche; Christophe Bosc; Manon De Andrade; Eric Denarier; Gregory Effantin; Annie Andrieux; Sylvie Gory-Fauré; Laurence Serre; Isabelle Arnal (Nature Communications)
Abstract Most eukaryotic cells have cilia that serve vital functions in sensing, signalling, motility. The core architecture of cilia is an array of microtubule doublets, which consist of a complete A-tubule and an incomplete B-tubule. How these structures assemble remains poorly understood. Using total internal reflection fluorescence microscopy and cryo-electron tomography, we investigate the role of MAP6d1, a brain-specific protein containing microtubule lumen-targeting Mn-motifs. We show that MAP6d1 assembles stable microtubule doublets by recruiting tubulin dimers onto the A-tubule lattice to initiate B-tubule nucleation. MAP6d1 also promotes the formation of luminal protofilaments in singlet and doublet microtubules, a previously undescribed phenomenon that likely enhances microtubule stability. In neurons, MAP6d1 localises to the proximal part of primary cilia via its Mn-motif, with its loss resulting in shortened cilia, a characteristic of ciliopathies. MAP6d1 is thus a neuronal Mn-motif protein with a specific role in assembling microtubule doublets and regulating ciliary length.